Pengaruh Kebijakan Dividen, Kebijakan Hutang, dan Board Study Diversity terhadap Nilai Perusahaan: Studi Kasus pada Perusahaan Sektor Healthcare yang Terdaftar pada Bursa Efek Indonesia Periode 2018-2022 - Faisal Nur Falah; Dwi Urip Wardoyo (ManBiz: Journal of Management and Business, 2024)
The Healthcare sector is known to have experienced various dynamics in the last five years, including during the pandemic since 2020, which has had implications for financial performance and company value. This research aims to examine and analyze the influence of dividend policy, debt policy, and board study diversity on company value. Data was obtained using secondary data from companies in the healthcare sector listed on the Indonesia Stock Exchange for the period 2018 to 2022. Purposive sampling was used as a technique in this research, then a total of 5 final samples of companies were obtained after removing outlier data from the research object. Firm value is measured using the Tobin's Q method. The DPR ratio is used to measure dividend policy, while DER is used to measure debt policy, and Board Study Diversity is measured based on the ratio of board of directors with a background in economics and business studies compared to the total board of directors using panel data regression. Eviews. Test classical assumptions and test hypotheses with partial tests and simultaneous tests. This research explains that dividend policy has a positive and significant effect on company value, debt policy has a negative and significant effect on company value, while Board Study Diversity has no significant effect on company value. It is hoped that the company can improve its investment strategy in the policies it takes to ensure stability and increase company value.